Management practices and contribution of village chickens to livelihoods of communal farmers: The case of Centane and Mount Frere in Eastern Cape, South Africa - Busisiwe Gunya; Voster Muchenje; Masibonge Gxasheka; Thobela Tyasi; Patrick Masika (Society for Indonesian Biodiversity, 2020)
Abstract. Gunya B, Muchenje V, Gxasheka M, Tyasi LT, Masika PJ. 2020. Management practices and contribution of village chickens to livelihoods of communal farmers: The case of Centane and Mount Frere in Eastern Cape, South Africa. Biodiversitas 21: 1345-1351. This study was conducted to determine village chickens production practices and their contribution to the livelihoods of farmers in rural households of the Eastern Cape Province, South Africa. Data were gathered using a questionnaire survey of 150 households, which were identified by the use of snowball sampling. Village chickens were the most livestock species kept by farmers, mostly owned by women (79.61% in Centane and 81.06% in Mount Frere) and were kept for household food needs. Some farmers (21.92% and 25.31%) also occasionally sold their chickens at an average of R80 (7.22) per bird. Most (93.13% and 76.44%) chickens flocks were provided with supplementary feed. The majority of farmers (80.31% and 88.33%) provided shelter for their chickens. The causes of chicken losses were reported to be diseases, predators, parasites and theft. The most cited disease problem was Newcastle (50.32% and 66.02%) while major predators were eagles (84.91% and 81.82%). The most common internal parasites were roundworms and tapeworm whilst the most reported external parasites were poultry lice and mites. The majority of farmers (94.51% and 92.21%) reported using chicken manure to improve the fertility of soils in their gardens. Chickens had a varied social role in the two areas, i.e., donation (61.63% and 68.82%) to neighbors and relatives. The majority of farmers (84.90%) in Centane didn't use chickens for cultural purposes whilst the majority (55.85%) in Mount Frere used chickens for cultural purposes. The present study showed that village chickens have a contribution to the livelihoods of rural households.